Validation of implant stability: A measure of implant permanence - Neha Mall; B Dhanasekar; I N Aparna (Wolters Kluwer Medknow Publications, 2011)
Implant stability is a requisite characteristic of osseointegration. Without it, long-term success cannot be achieved. Continuous monitoring in a quantitative and objective manner is important to determine the status of implant stability. Measurement of implant stability is a valuable tool for making decisions pertaining to treatment protocol and also improves dentist-patient communication. Owing to the invasive nature of histological analysis, various others methods have been proposed like radiographs, cutting torque resistance, reverse torque, modal analysis, resonance frequency analysis and Implatest® . This review focuses on objectives and various methods to evaluate implant stability.